(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify the impact of hypersensitivity on the psychological and social adjustment of special education students at Al-Rand and Al-Sahel Al-Akhdar Schools. The researcher relied on the descriptive correlational approach, and the study sample consisted of (40) male and female students. What are the statistical methods? Pearson’s correlation coefficient T-test for one sample T-test for two controlled samples What is the methodology? The researcher used the descriptive analysis approach. What are the results of the research? Hypersensitivity among below-average special education students